Impact of Left Ventricular Assist Devices on Quality of Life in End-Stage Heart Failure Patients: A Comprehensive Assessment - Mate, Ritesh; Surve, Sonali; Das, Satish; Rawekar, Kunal; Badkhal, Ashish; Lawande, Aneesh (Journal of Neonatal Surgery, 2025)
Introduction: Left Ventricular Assist Devices (LVADs) are crucial treatments for end-stage heart failure patients, either as a bridge to heart transplantation or as a long-term solution. This study evaluates the impact of LVAD therapy on quality of life (QOL), focusing on both physical and psychological outcomes. Methods: The study assessed QOL using multiple measures: the EQ-5D for general health, PHQ-9 for depressive symptoms, Heart Muscle Recovery Score (HMRS) for cardiac function, and the 6-Minute Walk Test (6MWT) for functional capacity. Data was collected from multiple clinical studies, and the results were analyzed to determine improvements in physical and mental health post-LVAD implantation. Results: LVAD implantation led to significant improvements in physical health, as demonstrated by increased endurance and functional capacity in the 6MWT. Cardiac function recovery was also noted, with a marked improvement in heart muscle recovery. In terms of psychological health, depressive symptoms remained a concern, with varying levels of depression observed in different studies. While some patients showed mild symptoms of depression, others reported more significant psychological distress. The EQ-5D scores indicated moderate to significant improvements in overall health-related QOL. Conclusion: LVAD therapy significantly improves physical health and functional capacity in end-stage heart failure patients. However, mental health issues, particularly depression, persist in some patients, highlighting the need for ongoing psychological support. Integrating mental health care into LVAD management is essential for optimizing patient outcomes. Further research is needed to better understand the long-term psychological effects of LVAD therapy. significant therapeutic interventions. Moreover, DDS is the latest advanced technological to overcome the limitations of the existing drug administration’s such as bioavailability, low solubility, abbreviated half-life, etc. Here, this study discusses the recent technologies which based on healthcare innovation related models are explored